(untitled) (Ius Novum, 2021)
The article carries out an analysis of resolutions and rulings of the supreme Court Criminal Chamber passed as a result of appellate courts’ requests for fundamental interpretation of a statute within the scope of substantive criminal law. the analysis covers: the method of extraordinary mitigation of a penalty for felonies carrying cumulative deprivation of liberty and a fine (article 60 § 2 CC); a conditionally suspended cumulative penalty of deprivation of liberty and a penalty of limitation of liberty (article 87 § 1 CC), and admissibility of cumulating the penalty of deprivation of liberty and the penalty of limitation of liberty that substitutes for a conditionally suspended penalty of deprivation of liberty (article 75a § 1 CC); liability for an offence of failing to pay alimony (article 209 § 1 CC) connected with the modification of its statutory features laid down in act of 23 March 2017; the issue of parents’ liability for the offence of kidnapping or detaining a minor under the age of 15 or a physically or mentally disabled person against the will of a person granted the rights of their caretaker or guardian (article 211 CC).